STRATEGI PENGELOLAAN TERIPANG BERBASIS KELEMBAGAAN PENGELOLA SASI DI KECAMATAN ARU UTARA TIMUR - Koritelu, Christian; Lopulalan, Yoisye; Nanlohy, Hellen (TRITON: Jurnal Manajemen Sumberdaya Perairan, 2025)
Sasi laut in Maluku is a local wisdom tradition that has been practiced to preserve marine resources. One of the marine resources in Aru Islands Regency that is preserved through the sasi system is sea cucumbers. In the implementation of sasi, several problems were found, including the opening of sasi, lack of rule enforcement, lack of community understanding and the limited role of customary institutions. The purpose of this research is to formulate an institutional-based sea cucumber management strategy in Aru Utara Timur sub-district. This research was conducted from November 2023 to June 2024 in Aru Utara Timur Subdistrict. Data collection was conducted by interview method using questionnaires to 25 respondents. Interviews were also conducted with key informants consisting of village leaders, customary leaders, and community representatives. The data obtained were analyzed using A'WOT which is a combination of AHP and SWOT. Based on the results of the research, there are several strategies that can be applied, namely optimizing the potential of sea cucumber resources; forming sea cucumber business groups; opening business opportunities for investors; optimizing sea cucumber sasi management institutions; conducting regular socialization activities to the community about sea cucumber resources; building cooperation between village institutions and the government, private sector and NGOs; expanding market access; increasing monitoring of resources during sasi closure; building good communication between institutions; providing strict legal sanctions for rule breakers; socializing environmentally friendly technology, and increasing synergy between related institutions. ABSTRAK Sasi laut di Maluku merupakan sebuah tradisi kearifan lokal yang telah dipraktikkan untuk menjaga kelestarian sumberdaya laut. Salah satu sumberdaya laut di Kabupaten Kepulauan Aru yang dilestarikan melalui sistem sasi yaitu teripang. Dalam pelaksanaan sasi ditemukan beberapa permasalahan antara lain pembukaan sasi, kurangnya penegakan aturan, kurangnya pemahaman masyarakat dan keterbatasan peran lembaga adat. Tujuan penelitian ini adalah memformulasikan strategi pengelolaan teripang yang berbasis pada kelembagaan di Kecamatan Aru Utara Timur. Penelitian ini dilakukan pada November 2023 hingga Juni 2024 di Kecamatan Aru Utara Timur. Pengumpulan data dilakukan dengan metode wawancara menggunakan kuesioner kepada 25 responden. Wawancara juga dilakukan kepada informan kunci yang terdiri dari pimpinan desa, pemangku adat, serta perwakilan masyarakat. Data yang diperoleh dianalisis menggunakan A’WOT yang merupakan kombinasi antara AHP dan SWOT. Berdasarkan hasil penelitian diperoleh beberapa strategi yang dapat diterapkan yaitu mengoptimalkan potensi sumberdaya teripang; membentuk kelompok usaha teripang; membuka kesempatan usaha bagi investor; mengoptimalkan kelembagaan pengelola sasi teripang; melakukan kegiatan sosialisasi secara rutin kepada masyarakat tentang sumberdaya teripang; membangun kerjasama antar lembaga desa dan pemerintah, swasta dan NGO; memperluas akses pasar; meningkatkan pengawasan terhadap sumberdaya saat penutupan sasi; membangun komunikasi yang baik antar lembaga; memberikan sanksi hukum yang tegas bagi pelanggar aturan; mensosialisasikan teknologi ramah lingkungan, serta meningkatkan sinergisitas antar lembaga terkait. Kata Kunci: Strategi, pengelolaan, teripang, kelembagaan, sasi